FAKTOR-FAKTOR YANG MEMPENGARUHI ADOPSI INOVASI POLA KEMITRAAN AGRIBISNIS SAYURAN DI JAWA BARAT - Ninuk Purnaningsih; Basita Ginting; Margono Slamet; Asep Saefuddin; Soedijanto Padmowihardjo (Jurnal Penyuluhan, 2006)
The objectives of this research was: to understand the farmers decision-making process in accepting the agribusiness joint venture company, to explore the factors relating to the farmers decision-making, and to analyze changes in farmer companies’s performances and a co-operative in Bogor, Cianjur, Bandung, and Garut. The population of the study was 285 farmers. The dissemination of Farmers decision to get involve in joint venture companies occurred through farmers to farmers interaction, and through their familyties. Some encouraging factor that affected farmers to joint the joint venture companies were guaranteed marketing, supply of seeds, manure, and pesticide, high vegetable productivity, extensiion agent’s technical assistance, and following other farmers.